Clinical Research on the Ophthalmic Factors Affecting 3D Asthenopia - Kim, Seung-Hyun; Suh, Young-Woo; Song, Jong-Suk; Park, Ji-Hye; Kim, Yong Yeon; Huh, Kuhl; Son, Jaebum; Kham, Keetaek; Jeong, Taeuk; Pyo, Kyung Soo (Journal of Pediatric Ophthalmology & Strabismus, 2012)
Purpose: Watching three-dimensional (3D) images is known to induce ocular and non-ocular symptoms, such as eye discomfort, fatigue, headache, and nausea, which can be referred to as “3D asthenopia”. This study investigated ophthalmic factors associated with 3D asthenopia. Methods: One hundred fifteen volunteers, aged 18 to 55 years, were enrolled in this study. 3D images were shown to all volunteers with 3D high-definition television for 90 minutes. Subjects who felt eyestrain were assigned to the asthenopia group (14 subjects) and subjects without symptoms were assigned to the control group (22 subjects). Ophthalmic factors including visual acuity, refractive errors, interpupillary distance, intraocular pressure, tear break-up time, near point of accommodation, presence of strabismus, stereoacuity, and retinal abnormalities were evaluated and compared between the two groups. Results: Six subjects in the asthenopia group had exophoria and 1 subject in the control group had constant exotropia. None of these participants had previously noticed symptoms of strabismus. Only the presence of strabismus was significantly different between the groups (Six subjects in the asthenopia group had exophoria and 1 subject in the control group had constant exotropia. None of these participants had previously noticed symptoms of strabismus. Only the presence of strabismus was significantly different between the groups ( P = .008). Conclusion: The presence of exophoria may be a risk factor for 3D asthenopia, and 3D television may induce asthenopia by exacerbating this latent problem.